Phase stability and mechanical properties of wire + arc additively manufactured H13 tool steel at elevated temperatures. (20th March 2021) - Tanvir, A.N.M.; Ahsan, Md. R.U.; Seo, Gijeong; Bates, Brian; Lee, Chanho; Liaw, Peter K.; Noakes, Mark; Nycz, Andrzej; Ji, Changwook; Kim, Duck Bong
Abstract: Wire + arc additive manufacturing (WAAM) is considered an innovative technology that can change the manufacturing landscape in the near future. WAAM offers the benefits of inexpensive initial system setup and a high deposition rate for fabricating medium- and large-sized parts such as die-casting tools. In this study, AISI H13 tool steel, a popular die-casting tool metal, is manufactured by cold metal transfer (CMT)-based WAAM and is then comprehensively analyzed for its microstructural and mechanical properties. Location-dependent phase combinations are observed, which could be explained by nonequilibrium thermal cycles that resulted from the layer-by-layer stacking mechanism used in WAAM. In addition, remelting and reheating of the layers reduces welding anomalies (e.g., pores and voids). The metallurgical characteristics of the H13 strongly correlate with the mechanical properties. The combinations of phases at different locations of the additively manufactured part exhibit a periodic microhardness profile. Martensite, Retained Austenite, Ferrite, and Carbide phases are found in combination at different locations of the part based on the part's temperature distribution during additive deposition. Moreover, the tensile properties at elevated temperatures (23 °C, 300 °C, and 600 °C) are comparable to those from other WAAM and additive manufacturing (AM) processes. The X-ray diffraction results verify that the microstructural stability of the fabricated parts at high temperatures would allow them to be used in high temperatures.